2016
DOI: 10.3390/ijms17071023
|View full text |Cite
|
Sign up to set email alerts
|

Roles of d-Amino Acids on the Bioactivity of Host Defense Peptides

Abstract: Host defense peptides (HDPs) are positively-charged and amphipathic components of the innate immune system that have demonstrated great potential to become the next generation of broad spectrum therapeutic agents effective against a vast array of pathogens and tumor. As such, many approaches have been taken to improve the therapeutic efficacy of HDPs. Amongst these methods, the incorporation of d-amino acids (d-AA) is an approach that has demonstrated consistent success in improving HDPs. Although, virtually a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 145 publications
(246 reference statements)
4
51
0
1
Order By: Relevance
“…The observation made in this study is consistent with previous experimental results of Oren and Shai (1997), which stipulates that hydrophobicity and charge are the primary determinants of antimicrobial activities of AMPs. The same observation was made by a number of research and review articles (Čeřovský et al, 2008;Li et al, 2016;Toro Segovia et al, 2017) where all of which made the observation that positive charge and amphipahicity was important for AMP antimicrobial activity. In fact, positive charge is a key recognition feature of AMPs and antimicrobial activity could be significantly increased by simply adding more positively charged amino acids to the peptides (Papo and Y, 2003).…”
Section: Global Descriptor Detailssupporting
confidence: 53%
See 1 more Smart Citation
“…The observation made in this study is consistent with previous experimental results of Oren and Shai (1997), which stipulates that hydrophobicity and charge are the primary determinants of antimicrobial activities of AMPs. The same observation was made by a number of research and review articles (Čeřovský et al, 2008;Li et al, 2016;Toro Segovia et al, 2017) where all of which made the observation that positive charge and amphipahicity was important for AMP antimicrobial activity. In fact, positive charge is a key recognition feature of AMPs and antimicrobial activity could be significantly increased by simply adding more positively charged amino acids to the peptides (Papo and Y, 2003).…”
Section: Global Descriptor Detailssupporting
confidence: 53%
“…In previous articles (Li et al, 2016;Shoombuatong et al, 2018), we had investigated the field of HDP extensively and can attest that there is a plethora of computational studies on HDPs investigating the classification of HDPs on the basis of their target pathogen class (e.g. bacteria, cancer, parasites, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…28). In this study we found that D-form KLKLLLLLKLK-NH 2 showed higher antimicrobial activity against both Gram-positive and Gram-negative bacteria, including S. aureus and E. coli , relative to its L-form counterpart.…”
Section: Discussionmentioning
confidence: 99%
“…Because AMPs typically do not exert their direct antibiotic activity by specific structural affinities, dynamic metabolic stability can be gained by assembling the prodrug sequence from heterochiral residues. Thus, the AMP itself is assembled from D‐amino acids, whereas the promoiety and linker are made of L‐amino acids . For example, fusion sequences encompassing an oligo‐glutamate, a neutrophil elastase (NE)‐sensitive tetrapeptide motif (AAAG), and an all‐D AMP could target Pseudomonas aeruginosa in chronically infected cystic fibrosis (CF) patients.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the AMP itself is assembled from D-amino acids, whereas the promoiety and linker are made of L-amino acids. 21 For example, fusion sequences encompassing an oligo-glutamate, a neutrophil elastase (NE)-sensitive tetrapeptide motif (AAAG), and an all-D AMP could target Pseudomonas aeruginosa in chronically infected cystic fibrosis (CF) patients. These prodrug candidates can confine the activity of linear AMPs to the endobronchial space and reduce the toxicity of their parent peptides in vivo.…”
mentioning
confidence: 99%